Genomic and epidemiological analysis of SARS-CoV-2 variants isolated in Guinea: a routine sequencing implementation - Aminata Mbaye; Haby Diallo; Thibaut Armel Cherif Gnimadi; Kadio Jean Jacques Olivier Kadio; Abdoul Karim Soumah; Joel Balle Koivogui; Jean Louis Monemou; Moriba Kowa Povogui; Djiba Kaba; Castro Hounmenou; Laetitia Serrano; Christelle Butel; et al. (BMC Infectious Diseases)
Abstract Background Several variants of SARS-CoV-2 have a demonstrated impact on public health, including high and increased transmissibility, severity of infection, and immune escape. Therefore, this study aimed to determine the SARS-CoV-2 lineages and better characterize the dynamics of the pandemic during the different waves in Guinea. Methods Whole genome sequencing of 363 samples with PCR cycle threshold (Ct) values under thirty was undertaken between May 2020 and May 2023. The Illumina iSeq 100 technology was used. The sequences were then analyzed using the GeVarli pipeline to generate consensus sequences and variant calling. All sequences isolated in Guinea and available on GISAID were included in the analysis for phylogenetic tree and phylodynamic determination. Nextstain tools were used for these analyses. Statistical analysis was done using GraphPad Prism version 10. Results The circulation of SARS-CoV-2 in Guinea can be distributed in three different periods. The first, lasting from May to June 2020, was characterized by lineages B1 and B.1.1. The second period, from January 2021 to July 2021, was characterized by the lineages B.1.1.7 (Alpha), AY.122, B.1.1.318, R1, B.1.525 and B.1.629. The third period, between December 2021 and May 2023, was characterized by the Omicron variant, with nine subvariant majorities found. In addition, detecting variants in the period out of their circulation was documented. The importation and exportation investigation showed the strong movement viral association between Guinea and Senegal on the one hand and Guinea and Nigeria on the other. Conclusion In summary, this study contributes to understanding the epidemic dynamics of the disease by describing the significant variants that circulated in Guinee and the distribution of this variant in the population. It also shows the importation and exportation of the virus during the pandemic. Sub-sampling and degradation of samples for sequences were observed. Organization and collaboration between laboratories are needed for a good sample-collecting and storage system for future direction.